2020
DOI: 10.1590/2175-7860202071055
|View full text |Cite
|
Sign up to set email alerts
|

A chemophenetic study of the genus Maytenus s.l. (Celastraceae): contribution to the rational search of its bioactive metabolites

Abstract: Maytenus s.l. is a genus of the Celastraceae family and many of its species are used in traditional medicine. Most of the substances responsible for the biological activities of plants come from their secondary metabolism, such as terpenoids and flavonoids, which have multiple functions in the plant and can occur in a similar way in plant groups. Chemophenetics analyzes the occurrence of these substances in a taxon and can infer evolutionary trends and contribute to the rational search for new drugs. Chemosyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Phytochemical studies have made it possible to identify flavonoids, pentacyclic triterpenes (friedelane-, oleane-, lupane-, and ursane-type), sesquiterpenes, alkaloids and condensed tannins. Antiulcer, anti-inflammatory, contraceptive, antioxidant, antimicrobial, antiviral, and antiparasitic activities have been reported (Biral et al 2017, Guimarães et al 2020, Lei et al 2020, Niero et al 2011, Veloso et al 2017, Zhang et al 2020. Recent research has confirmed the activity of the hexanic extract from the bark of Maytenus guianensis against leishmaniasis.…”
Section: Introductionmentioning
confidence: 97%
“…Phytochemical studies have made it possible to identify flavonoids, pentacyclic triterpenes (friedelane-, oleane-, lupane-, and ursane-type), sesquiterpenes, alkaloids and condensed tannins. Antiulcer, anti-inflammatory, contraceptive, antioxidant, antimicrobial, antiviral, and antiparasitic activities have been reported (Biral et al 2017, Guimarães et al 2020, Lei et al 2020, Niero et al 2011, Veloso et al 2017, Zhang et al 2020. Recent research has confirmed the activity of the hexanic extract from the bark of Maytenus guianensis against leishmaniasis.…”
Section: Introductionmentioning
confidence: 97%